Implementasi Simple Moving Average dan Exponential Moving Average dalam Menentukan Tren Harga Saham Perusahaan - David Widodo; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
The rapid economic growth, technology and science have a big impact on human mind for searching and getting money, one of the example is stocks investment. The information is so easy to find and disseminated, as well as the awareness and knowledge are the other key to be able to know and understand how to be a good investor. The purpose of this research was to implement simple moving average and exponential moving average to determine the trend of the stock price of a company. The application is by calculating the value of a simple moving average and exponential moving average period of 5 (weekly) and a period of 20 (monthly) then analyze the results of calculation with the data on the fact whether it is appropriate or not. The tests for this research is conducted using data from the 15 companies listed in the Indonesia Stock Exchange (IDX) and always included in the list of LQ45 index from 2005 to 2014. From the research that began on January 6, 2014 until September 29, 2015 for the simple moving average and the exponential moving average period of 5 (weekly) can be inferred that the level of accuracy of the simple moving average 5-day period was at 61,73%, then to the result of the exponential moving average 5-day period was at 68,07%. Then, based on research results that starting on January 1, 2014 until September 29, 2015 for the simple moving average and the exponential moving average 20day period (monthly) can be inferred that the level of accuracy of the simple moving average 20-day period was at 72,52%, and then to result 20-day period exponential moving average is at 73,39%.